Pelaksanaan Pencatatan Hak Kekayaan Intelektual Batik Tulis Berbasis Pendidikan Karakter - Belinda Dewi Regina; Innany Mukhlishina; Yohana Puspitasari Wardoyo (Jurnal Pengabdian Pada Masyarakat, 2020)
IMPLEMENTATION OF RECORDING OF INTELLECTUAL PROPERTY OF BATIK WRITING BASED ON CHARACTER EDUCATION. Pujon Kidul Tourism Village located in Malang Regency has unspoiled potential and is suitable for educational tourism. Activities undertaken in tourism education are vegetable picking, animal husbandry, milk processing, outbound, rice field cafes, and handicrafts that can improve the lives of the local residents. One of the business opportunities that the Pujon Kidul community has begun to develop is batik, but there are still only a few people who have batik knowledge and character, they only make it without knowing the meaning of the resulting motif. The motifs that are widely used in batik are images of dragonflies, mountains, rice, and huts as a natural feature of the tourism village. During this time the community is very worried that there will be attention, extinction, appreciation from others for the batik motifs that have been produced. Therefore, the UMM community service team asked for assistance from the Tourism Village to support the assistance of Intellectual Property Rights on Batik motifs produced by the Pujon Kidul Tourism Village through the Director General of Intellectual Property Rights. So that it can foster the entrepreneurial spirit of the village community marked by the village community. which produces written batik based on character education and distributes tourism areas, therefore the tourist area will facilitate written batik produced by the people of Pujon Kidul Village, which has their natural beauty.